Estimation of litter mass in nongrowing seasons in arid grasslands using MODIS satellite data. Issue 1 (1st January 2018) - Ren, Hongrui; Zhang, Bei; Guo, Xulin
ABSTRACT: Litter has a special ecological functioningin grasslands. Few studies have been conducted to estimate litter mass using remotely sensed data during nongrowing seasons in arid grasslands although it is important forage for livestock sustainability. With MODIS data, estimation methods were developed for litter mass in the desert steppe of Inner Mongolia calibrated with field surveys. As MODIS Band 7 is located in the lignocellulose absorption pit of litter near 2100 nm, the best models were obtained for NDTI (normalized difference tillage index) (normalized difference between Bands 6 and 7) and STI (soil tillage index) (ratio of Band 6–7) among soil-unadjusted indices, and for MSACRI (modified soil-adjusted crop residue index) (modification of NDTI by incorporating soil line) among soil-adjusted indices. NDTI and STI explained 63% of the variance of litter mass, while MSACRI explained 71% of the variance. If data are not available for calculating soil line, it may be appropriate to use the soil-adjusted NDTI (S-NDTI), a new index proposed in the study that incorporates a soil adjustment factor into the NDTI equation. The optimal S-NDTI explained 66% of the variance. The NDTI, STI, MSACRI and S-NDTI can be applied to estimate litter mass in arid grasslands.